Deficiency in post-adoption social work in Tabasco (Revista de Investigaciones Universidad del Quindío, 2020)
The constant changes in social behavior, ranging from the tendency of couples not to get married to the erratic behavior of the human personality, we see that it is less and less possible for people to choose adoption as a method of having children; And if we add to that that our legislation is long, not to say difficult procedures in its system for a couple to reach the adoption of a person, minor or not, because the process for this purpose is even more difficult. Of course, this arduous journey has a good reason. The State, in its eagerness to seek at all times the formation of the family and create a bond, originated in marriage, watches over the interests of all members, and in the particular case of adoption, puts the good of the minor before the needs of the others, in this case, the adopters.
Keywords: Adoption; integral development; family; social work